Viewpoint: Environmental Slogans: Memes with Diverging Interpretations - Christo Fabricius; Samantha McCulloch (Environmental Association of Southern Africa, 2016)
Environmental slogans can be seen as memes, i.e. cultural constructs that, not unlike genes, replicate themselves from one generation to the next. Memes may, however, be divergently interpreted and some memes can even have unwanted side-effects. We wanted to find out how supporters of an environmental non-governmental organisation (NGO) interpreted their slogan 'People Caring for the Earth'. During a celebratory event of one of the NGO's branches we asked 65 supporters of the organisation to write down their interpretation of the meaning of the slogan, as well as the actions that they regularly engage in to give substance to it. Fifty-eight per cent of the 34 respondents gave social-ecological systems interpretations of 'Caring for the Earth' and interpreted it as humans living sustainably with nature. Their associated actions centred around sustainable living principles. Forty-two per cent of respondents held strong naturecentric interpretations of the slogan, understanding it as a call to conserve species and ecosystems. Their associated actions centred around awareness raising and educating others. While these were broad patterns rather than exclusive, distinct categories, our results suggest that environmental memes should be used with circumspection, that their meaning should be clarified through actions rather than words, and that organisations should give as much attention to the meaning of their slogan as they do to the environmental causes they aim to address. The way environmental slogans are perpetuated within an organisation has implications for the membership they attract or deter.